A Nursing School on Reservation Land. Issue 12 (December 2022) - Wilson, Deborah; Werk, Alicia; Hemmer, Brigit
ABSTRACT: An associate degree in nursing program was established six years ago at the tribal college of the Fort Belknap Indian Reservation, home of the Aaniiih and Nakoda people. As this program continues to evolve and grow, it offers a successful example of how to increase diversity in nursing and potentially improve the health outcomes of Native Americans living on and nearby reservation communities. Abstract : The authors describe the creation of the Grow Our Own associate degree in nursing program at the tribal college of the Fort Belknap Indian Reservation in Montana, an example of how to increase diversity in nursing and potentially improve the health outcomes of the Native Americans living on and nearby reservation communities.